Influence of Leadership Behavior and Management Process on Immunization Program Implementation - Br Pintubatu, Christina Delina; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: Indonesia is still ranked 4th in the world for having low DPT3 immunization coverage among children. Complete basic immunization coverage is targeted at 95% according to the strategic plan of Indonesian Ministry of Health, but it still achieves at 91.1%. This study aims to analyze leader behavior and health center management on immunization program implementation.Method: Quantitative research using a cross-sectional design was conducted at the Puskesmas Biru-Biru Deli Primary Healthcare Center, Serdang District. The research population and samples consist of 122 respondents which include all 121 midwives in 17 villages and one person in charge of immunization services. The survey data were analyzed using the chi-square test and logistic regression test.Results: The chi-square test showed an influence of leadership behavior and management process on immunization program implementation (p = 0.000). In the last stage of logistic regression analysis, one variable that most dominantly affected the program implementation is management process (p = 0.0000; OR = 25,497; 95% CI = 6.475-100.406). The primary healthcare center needs to improve leader’s behavior and management process.